Fetal goiter identified in a pregnant woman with triiodothyronine-predominant graves' disease: a case report - Akiko Fujishima; Akira Sato; Hiroshi Miura; Yuki Shimoda; Saeko Kameyama; Chika Ariake; Hiroyuki Adachi; Yuki Fukuoka; Yukihiro Terada (BMC, 2020)
Abstract Background Approximately 10% of all Graves' disease cases are triiodothyronine (T3)-predominant. T3-predominance is characterized by higher T3 levels than thyroxine (T4) levels. Thyroid stimulating hormone receptor autoantibody (TRAb) levels are higher in T3-predominant Graves' disease cases than in non-T3-predominant Graves' disease cases. Treatment with oral drugs is difficult. Here, we report a case of fetal goiter in a pregnant woman with T3-predominant Graves' disease. Case presentation A 31-year-old woman had unstable thyroid function during the third trimester of pregnancy, making it impossible to reduce her dosage of antithyroid medication. She was admitted to our hospital at 34 weeks of gestation owing to hydramnios and signs of threatened premature labor, and fetal goiter (thyromegaly) was detected. The dose of her antithyroid medication was reduced, based on the assumption that it had migrated to the fetus. Subsequently, the fetal goiter decreased in size, and the hydramnios improved. The patient underwent elective cesarean delivery at 36 weeks and 5 days of gestation. The infant presented with temporary symptoms of hyperthyroidism that improved over time. Conclusions The recommended perinatal management of Graves' disease is to adjust free T4 within a range from the upper limit of normal to a slightly elevated level in order to maintain the thyroid function of the fetus. However, in T3-predominant cases, free T4 levels may drop during the long-term course of the pregnancy owing to attempts to control the mother's symptoms of thyrotoxicosis. Little is known about the perinatal management and appropriate therapeutic strategy for T3-predominant cases and fetal goiter. Therefore, further investigation is necessary.